2022
DOI: 10.1038/s41467-021-27895-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional changes in the mammary gland during lactation revealed by single cell sequencing of cells from human milk

Abstract: Under normal conditions, the most significant expansion and differentiation of the adult mammary gland occurs in response to systemic reproductive hormones during pregnancy and lactation to enable milk synthesis and secretion to sustain the offspring. However, human mammary tissue remodelling that takes place during pregnancy and lactation remains poorly understood due to the challenge of acquiring samples. We report here single-cell transcriptomic analysis of 110,744 viable breast cells isolated from human mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 48 publications
7
46
0
Order By: Relevance
“…These subsets agree with other datasets describing scRNA-seq on hBM in smaller cohorts on the basis of component cell clusters and genes expressed in these clusters with some exceptions ( SI Appendix , Fig. S3 A – E ) ( 15 , 27 , 30 ). Due to increased cell numbers in this dataset, we identified more immune clusters (seven) than previous studies, which identified two or three clusters, adding dendritic cells, a second macrophage cluster, and eosinophils to these previously identified.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…These subsets agree with other datasets describing scRNA-seq on hBM in smaller cohorts on the basis of component cell clusters and genes expressed in these clusters with some exceptions ( SI Appendix , Fig. S3 A – E ) ( 15 , 27 , 30 ). Due to increased cell numbers in this dataset, we identified more immune clusters (seven) than previous studies, which identified two or three clusters, adding dendritic cells, a second macrophage cluster, and eosinophils to these previously identified.…”
Section: Resultssupporting
confidence: 88%
“…4 B and SI Appendix , Figs. S3 B , C , and F and S8 F ) ( 15 , 27 ). We found that all epithelial subclusters expressed genes related to milk synthesis—such as LALBA , CSN2 , XDH , and FASN , as well as canonical luminal cell markers ( EPCAM , KRT18 , KRT19 )—suggesting a clear luminal lineage and role in milk production ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations